Four new adelgid (Hemiptera: Adelgidae) species from Bhutan, including the first legless species of Aphidomorpha - Havill, Nathan P.; Brunet, Bryan; Zembrzuski, Zephyr; Tshering, Kaka (Zootaxa, 2025)
A new subgenus and four new species of Adelges (Hemiptera: Adelgidae) are described from Bhutan. To support their taxonomic placement, we provide a phylogeny of Adelgidae reconstructed using mitochondrial and nuclear DNA sequence data. Cassiadelges subgen. nov is distinguished by the combination of feeding on Larix secondary hosts, having tergites of the head and pronotum fused into a cephaloprothoracic shield, and having only acuminate setae on the terminal abdominal segments. Adelges (Cassiadelges) coccipus sp. nov. feeds on Larix griffithii. This remarkable species is the only known member of Aphidomorpha that is lacking legs. The first instar nymph has legs, while the second instar to adult have vestigial legs present as small cuticular protrusions with clusters of setae. Its discovery presents an exciting opportunity to examine the evolutionary development of insect limb formation from a new perspective. Adelges (Cholodkovskya) changaphuensis sp. nov. feeds and forms galls on Picea spinulosa. Adelges (Aphrastasia) densae sp. nov. feeds on Abies densa. This may be the same as what was reported on this host in 1985 as Chermes abietispiceae Stebbing (nomen dubium). Adelges (Annandina) lepsimon sp. nov. feeds on Tsuga dumosa. It is separated from the only other member of its subgenus, Adelges (Annandina) tsugae Annand, by first instar exules having a pair of prominent anterior cephalic wax glands. It feeds between the needles on twigs in a similar fashion to A. (An.) tsugae Annand, which is also found in Bhutan, making it difficult to distinguish them in the field.